OBSERVATIONS ON THE RELATIONSHIP BETWEEN NEUROSECRETION AND PERIODIC ACTIVITY IN THE MUSSEL, PARREYSIA CORRUGATA - Nagabhushanam, R; Lomte, V S (Indian Journal of Fisheries, 2011)
Two types of 'neurosecretory cells in the freshwater mussel Parreysia corrugataare briefly described. The cell type A which is pyrifown secretes materialin the fomm of colloid. The cell type B is oval and; the secretory material is in thefoirm of fine grawutea Im both the ceW types transport of the secretiary materielwas noticed. Type A cells showed a distinct annual cycle of activity that iscorrelated to the sexual cycle.